2006
DOI: 10.1073/pnas.0602750103
|View full text |Cite
|
Sign up to set email alerts
|

Broad activation of the olfactory bulb produces long-lasting changes in odor perception

Abstract: A number of electrophysiological experiments have shown that odor exposure alone, unaccompanied by behavioral training, changes the response patterns of neurons in the olfactory bulb. As a consequence of these changes, across mitral cells in the olfactory bulb, individual odors should be better discriminated because of previous exposure. We have previously shown that a daily 2-h exposure to odorants during 2 weeks enhances rats' ability to discriminate between chemically similar odorants. Here, we first show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
98
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 49 publications
4
98
0
1
Order By: Relevance
“…We have shown that odor enrichment enhances rats' ability to discriminate between chemically similar odorants in a relatively odor-unspecific manner (5,6). Indeed, the discrimination of a pair of similar odorants is improved by enrichment with the same odorants or with other odorants that activate regions of the OB partially overlapping with the regions activated by the discriminated pair.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…We have shown that odor enrichment enhances rats' ability to discriminate between chemically similar odorants in a relatively odor-unspecific manner (5,6). Indeed, the discrimination of a pair of similar odorants is improved by enrichment with the same odorants or with other odorants that activate regions of the OB partially overlapping with the regions activated by the discriminated pair.…”
mentioning
confidence: 95%
“…For instance, animals trained on a tactile discrimination task improve their behavioral performances and in parallel, the neural representation of the stimuli is sharpened (2,3). In the olfactory modality, perceptual learning has been shown to occur in humans (4), and an experimental model of olfactory perceptual learning has recently been proposed in rats (5). Olfactory perceptual learning is crucial for basic olfactory functions because it sets the degree of discrimination between stimuli, and thus contributes to the perceptual representation of the environment, which guides the animal's behavior.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although early bulb ablation studies, most of which were not guided by knowledge of actual odorant responses, questioned the relevance of domain organization in the olfactory bulb, more recent interventive experiments have confirmed the critical involvement of spatially restricted regions in the perception of particular odorants. Pharmacological blockade of dorsal bulbar activity interferes with experiencedependent modification of responses to odorants whose activity involves those dorsal regions, but it does not affect responses to odorants activating only the ventral part of the bulb (9). Chemical ablation of particular domains in the epithelium diminishes responses to odorants expected to be represented in those regions but does not diminish responses to odorants expected to activate intact regions (10).…”
mentioning
confidence: 99%